Renal Function and Ultrasound Imaging in Elderly Subjects - Luca Zanoli; Giulia Romano; Marcello Romano; Stefania Rastelli; Francesco Rapisarda; Antonio Granata; Pasquale Fatuzzo; Mariano Malaguarnera; Pietro Castellino (The Scientific World Journal)
We evaluated in elderly subjects (a) the ability of GFR formulas to discriminate chronic kidney disease (CKD), (b) the correlation between renal morphology and function, and (c) the usefulness of combined r-US and GFR formulas to detect CKD. A total of 72 patients were enrolled (mean age 80 ± 7 years, male sex 44%, serum creatinine 0.98 ± 0.42 mg/dL, and CKD 57%). Cockcroft-Gault showed the highest sensitivity (78%) and specificity (94%) for CKD and was correlated with kidney volume (R=0.68, P<0.001). All formulas failed to provide a reliable estimate of GFR. In multivariate analysis, Cockcroft-Gault < 52 mL/min and kidney sinus section area < 28 cm2 showed the highest accuracy for the identification of CKD subjects (AUC 0.90, P<0.001). MDRD and CKD-EPI differed significantly for GFR ≥90 mL/min. Conclusions. Cockcroft-Gault < 52 mL/min was able to discriminate subjects with CKD but all formulas failed to provide a reliable estimate of GFR. The combined use of r-US and Cockcroft-Gault formula improved the ability to discriminate CKD in elderly subjects.